Effect of suckling on reproductive activities of Bunaji cows during the postpartum period - Eduvie, L.O.; Dawuda, P.M. (Cambridge University Press, 1986)
The effects of suckling on calving interval, intervals from calving to conception and pregnancy rate at 60 to 90 days postpartum are investigated. Forty-one cows were used, twelve of which were used to study serum concentrations during the postpartum period. The overall mean calving interval and interval from calving to conception for all cows were 426.7 and 146 days, respectively, with a conception rate of 48.8 percent. The serum progesterone concentrations of cows ranged from 0.1 to 6.9 ng/ml during the non-fertile cycle and 0.1 to 15 ng/ml at pregnancy. Suckling interfered with ovarian activities and thus conception during the postpartum period, resulting in a prolonged calving interval.